2011
DOI: 10.1097/olq.0b013e318224db39
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Antimicrobial Susceptibility Testing in Trichomonas vaginalis–Infected Women With Clinical Treatment Failure

Abstract: Clinical and microbiologic cure rates were higher for women who were treated in accordance with the recommendation provided after in vitro testing compared with those who received a lower dose or a different drug. Susceptibility testing leading to tailored treatment may have a beneficial role for management of women with persistent trichomoniasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
56
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 19 publications
0
56
0
Order By: Relevance
“…For example, one study linked resistance to infection of T. vaginalis by Mycoplasma (16); however, the mechanism by which infection would impart resistance is unclear, and this association was not found in a subsequent study (17). Another study found that infection by a double-stranded RNA virus was associated with a lower mean metronidazole MLC value (2); however, the virus is also strongly associated with population 1, being present in 73% of isolates in this population compared to only 2.5% of isolates in population 2 (18). Further studies will be required to determine the relative contribution of population ancestry, ntr Tv genotype, and other factors to metronidazole resistance.…”
mentioning
confidence: 85%
“…For example, one study linked resistance to infection of T. vaginalis by Mycoplasma (16); however, the mechanism by which infection would impart resistance is unclear, and this association was not found in a subsequent study (17). Another study found that infection by a double-stranded RNA virus was associated with a lower mean metronidazole MLC value (2); however, the virus is also strongly associated with population 1, being present in 73% of isolates in this population compared to only 2.5% of isolates in population 2 (18). Further studies will be required to determine the relative contribution of population ancestry, ntr Tv genotype, and other factors to metronidazole resistance.…”
mentioning
confidence: 85%
“…There are reports of dysuria, lower abdominal discomfort, itchiness of the vagina, leucorrhea, and vaginal odor in some women (Schwebke and Burgess 2004). Thus, Trichomonas vaginalis infection is usually only detected during routine STD screening (Bosserman et al 2011).…”
Section: Clinical Manifestation In Humansmentioning
confidence: 99%
“…Clinical and microbiological cure rates were higher in women with previous treatment failure who were treated in accordance with a treatment protocol utilising the results of a resistance test. 72 Resistance data from the UK are lacking due to the absence of a metronidazole resistance testing service; however in 2002, one group found a 3.5% prevalence of non-response to standard dose metronidazole in the absence of re-infection and nonadherence. 73 Clinical isolates resistant to metronidazole can be resistant to tinidazole but usually with significantly lower minimal lethal concentrations to tinidazole than metronidazole.…”
Section: Treatment Failurementioning
confidence: 99%
“…Paromomycin* intravaginally 250 mg once or twice daily for 14 days -56-58% cure rate reported 78,80 Furazolidone* intravaginally 100 mg twice daily for 12-14 days -33% cure rate reported 72,81 Acetarsol* pessaries 500 mg nocte for 2 weeks 6% Nonoxynol-9* pessaries nightly for 2 weeks Availability *The medicines suggested for use in treatment failure are unlicensed products and may not be readily available for purchase in the UK. The pharmacy purchasing department may be able to source some of these products from specialist manufacturers.…”
Section: Other Treatments With Some Reported Success (Evidence Level mentioning
confidence: 99%
See 1 more Smart Citation